Metode Pembelajaran Demonstrasi Dan Perumpamaan Takhrij Hadits Riwayat Al-Tirmidzi - Aulia, Roisatul; Suroyya, Himmatus; Syafiq, Muhammad Aunus; Qoyyimah, Layinatul; Khikmawati, Kholidah; Zulfahmi, Muhammad Nofan (Edification Journal : Pendidikan Agama Islam, 2023)
The phenomenon of the proliferation of the use of textual approaches only in the implementation of learning in educational institutions and teachers struggling to choose the right learning method in the field of study is a learning problem that exists in Indonesia. The purpose of this study is to find out: explanation of demonstration and parable learning methods based on the historical hadith of al-Tirmidzi. The research method used is the library research method with documentation techniques. Primary data sources come from the Book of Sunan Al-Tirmidzi and skunder data from previous theses, scientific articles and books relevant to the subject matter. Furthermore, it is analyzed using descriptive analysis techniques. From the results of the research, the demonstration methods and parables that have been practiced by the Prophet muhammad pbuh can be used as consideration for teachers in carrying out learning. The reason is that the delivery of the subject matter with demonstration and parable methods can increase the absorption of the material by students, time efficiency, easy to understand and fun so that the learning objectives that have been formulated can be achieved optimally.